British Scientific Journals in the Area of International Relations – 2017 Review - Jędrowiak, Patryk (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The text constitutes a review of articles published in 2017 on the pages of British academic journals dealing with international relations. The author has selected texts from issues of: “European Political Science Review”, “The British Journal of Politics and International Relations”, “Politics”, “Cambridge Review of International Relations” and “Political Studies.” The pre¬sented articles have been analyzed in the context of thematic groups such as: Brexit, elections, trust in politics, Middle East issues and others.

Tekst stanowi przegląd artykułów opublikowanych w 2017 roku na łamach brytyjskich czasopism naukowych odnoszących się do problematyki stosunków międzynarodowych. Autor wyselekcjonował teksty z następujących czasopism: „European Political Science Review”, „The British Journal of Politics and International Relations”, „Politics”, „Cambridge Review of International Relations” and „Political Studies.” Analiza tekstów została przedstawiona w ramach grup tematycznych takich jak: Brexit, wybory, zaufanie w polityce, kwestie bliskowschodnie oraz pozostałe tematy.
BRYTYJSKIE CZASOPISMA NAUKOWE Z OBSZARU STOSUNKÓW MIĘDZYNARODOWYCH – PRZEGLĄD 2017 ROKU
Keywords: journals review; Brexit; United Kingdom; elections; Middle East; China; Wielka Brytania; wybory; Bliski Wschód; Chiny; przegląd czasopism